Nano-puerarin regulates tumor microenvironment and facilitates chemo- and immunotherapy in murine triple negative breast cancer model. (March 2020) - Xu, Huan; Hu, Mengying; Liu, Mengrui; An, Sai; Guan, Kaiyun; Wang, Menglin; Li, Lei; Zhang, Jing; Li, Jun; Huang, Leaf
Abstract: Tumor associated fibroblasts (TAFs) are key stromal cells mediating the desmoplastic reaction and being partially responsible for the drug-resistance and immunosuppressive microenvironment formation in solid tumors. Delivery of genotoxic drugs off-targetedly to kill TAFs results in production of Wnt16 which renders the neighboring tumor cells drug resistant as shown in our previous study (PMC4623876). Our current approach looks for means to deactivate, rather than kill, TAFs. Reactive oxygen species (ROS) are the central hub of multiple profibrogenic pathways and indispensable for TAFs activation. Herein, puerarin was identified to effectively downregulate ROS production in the activated myofibroblast. In this study, a novel puerarin nanoemulsion (nanoPue) was developed to improve the solubility and bioavailability of puerarin. NanoPue significantly deactivated the stromal microenvironment (e.g., ~6-fold reduction of TAFs in nanoPue treated mice compared with the PBS control, p < 0.0001) and facilitated chemotherapy effect of nano-paclitaxel in the desmoplastic triple-negative breast cancer (TNBC) model. Moreover, the removal of the physical barrier increased intra-tumoral infiltration of cytotoxic T cell by 2-fold. This activated immune microenvironment allowed nanoPue to synergize PD-L1 blockade therapy in TNBC model.